Impact of Monetary Policy Transmission Mechanism in West African Countries - Famoroti , Jonathan Olusegun; Adeleke, Omolade (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The study analyzed the impact of monetary policy shocks on economic growth in 12 countries of the Economic Community of West African States (ECOWAS), using quarterly data from 1980(1) to 2017(4). We employed a Panel Structural Vector Autoregressive (Panel SVAR) for the modeling of monetary policy transmission shock in the segregated sub-regions of WAMZ and WAEMU. The key results suggest that fluctuations of the monetary policy do not have significant effects on the economic growth but significantly impact the general price level. Moreover, the study finds that the exchange rate is persistently a vital mechanism that significantly influences the variables of the real economy. Our estimates further suggest that there is idiosyncratic evidence found in the results, which is the anomaly of the Price puzzle.